Synthesis and Production of Activated Carbon from Sugarcane Bagasse for the Adsorptive Removal of Methylene Blue Dye from Wastewater - Kimpa, Mohammed Isah; Gene, Adamu Salahudeen; Ugochukwu, Stanley Chukwuebuka; Ojonugwa, Daniel Thomas; Isah, Haruna; Abdullahi, Fati; Fadipe, Labake Ajoke; Uno, Uno Essang (FUDMA Journal of Sciences, 2026)
A major global environmental challenge is water pollution from synthetic dyes. Conventional remediation techniques such as coagulation-flocculation, chemical oxidation, membrane filtration, ion exchange, and biological treatment can be expensive and frequently fail to effectively remove low pollution levels. The production and analysis of activated carbon from sugarcane bagasse (ScBAC) utilizing a chemical activation procedure with sulfuric acid (H2SO4) is the main objective of this study. The research assesses the material’s capacity to adsorb and extract methylene blue (MB) dye from wastewater. After carbonizing raw sugarcane bagasse at 250°C, it was steeped in H2SO4 for 24h at a 1:3 (w/v) ratio. The final product was properly described, dried in an oven, and carefully rinsed until neutral. Three primary phases of heat degradation were identified by thermogravimetric analysis (TGA), involving the breakdown of cellulose and hemicellulose between 200 and 450°C. ScBAC is primarily amorphous, with large peaks between 23–26° and 43° (2θ) that correspond to the disordered structure of graphitic carbon, using X-ray diffraction (XRD) research. According to Brunauer-Emmett-Teller (BET) measurements, the chemical activation significantly enhanced the material’s textural characteristics, raising the micropore volume from 0.096 to 0.225 cc/g and the specific surface area from 112.836 m²/g to 254.612 m²/g. ScBAC was able to eliminate up to 99.28% of MB and noted maximum adsorption capacity of 36.83mg/g in just 25 minutes of contact using 0.2 g ScBAC per 100 mL of 74.2 mg/L MB solution, in accordance with UV-visible spectrophotometry.